RF Positioning : Fundamentals, Applications, and Tools. - Campos, Rafael Saraiva (GNSS technology and applications series., 2015)
This new resource presents a comprehensive view of radio-frequency (RF) positioning. The book is organized to allow readers to progress at a fast pace, from the fundamentals of RF positioning, to the use of advanced tools such as artificial intelligence algorithms and application development environments. The first part of the book covers the fundamentals of RF localization. The second part addresses the application of those fundamentals in several types of wireless networks and technologies as Cellular Networks, Wi-Fi, Bluetooth, Sensor Networks, Ultra Wide Band, and Global Navigation Satellite Systems. The third part brings several tools to allow rapid development of positioning applications for mobile devices, as well as to support implementation, usage, deployment, and research of localization algorithms. This book presents numerous MATLAB examples, accompanied by the corresponding MATLAB code, made available at the book website. The MATLAB code to most figures is also provided, as well as databases of measurements collected during experiments conducted both in cellular and Wi-Fi networks. The book also is accompanied by Android source codes of the example apps developed in Chapter 10.